A glossary of theories for understanding power and policy for health equity. Issue 6 (20th March 2020) - Harris, Patrick; Baum, Fran; Friel, Sharon; Mackean, Tamara; Schram, Ashley; Townsend, Bel
Abstract : Progressing public policies that improve health equity requires understanding and addressing the creation, use and distribution of power. This glossary provides an overview of some of the most relevant conceptualisations of the dynamics of power in policy with implications for health equity. The aim is to provide an accessible overview of the different theories and perspectives behind power for public health focused policy researchers and advocates. The Glossary demonstrates how the broad literature on power in policy deepens understanding of the institutional dynamics that creates and maintains health inequities.